Efficacy of Servo-Controlled Splanchnic Venous Compression in the Treatment of Orthostatic Hypotension: A Randomized Comparison With Midodrine. Issue 2 (August 2016) - Okamoto, Luis E.; Diedrich, André; Baudenbacher, Franz J.; Harder, René; Whitfield, Jonathan S.; Iqbal, Fahad; Gamboa, Alfredo; Shibao, Cyndya A.; Black, Bonnie K.; Raj, Satish R.; Robertson, David; Biaggioni, Italo
Abstract : Splanchnic venous pooling is a major hemodynamic determinant of orthostatic hypotension, but is not specifically targeted by pressor agents, the mainstay of treatment. We developed an automated inflatable abdominal binder that provides sustained servo-controlled venous compression (40 mm Hg) and can be activated only on standing. We tested the efficacy of this device against placebo and compared it to midodrine in 19 autonomic failure patients randomized to receive either placebo, midodrine (2.5–10 mg), or placebo combined with binder on separate days in a single-blind, crossover study. Systolic blood pressure (SBP) was measured seated and standing before and 1-hour post medication; the binder was inflated immediately before standing. Only midodrine increased seated SBP (31±5 versus 9±4 placebo and 7±5 binder, P =0.003), whereas orthostatic tolerance (defined as area under the curve of upright SBP [AUCSBP ]) improved similarly with binder and midodrine (AUCSBP, 195±35 and 197±41 versus 19±38 mm Hg×minute for placebo; P =0.003). Orthostatic symptom burden decreased with the binder (from 21.9±3.6 to 16.3±3.1, P =0.032) and midodrine (from 25.6±3.4 to 14.2±3.3, P <0.001), but not with placebo (from 19.6±3.5 to 20.1±3.3, P =0.756). We also compared the combination of midodrine and binder with midodrine alone. The combination produced a greater increase in orthostatic tolerance (AUCSBP, 326±65 versus 140±53 mm Hg×minute for midodrine alone; P =0.028, n=21) and decreased orthostatic symptoms (from 21.8±3.2 to 12.9±2.9, P <0.001). In conclusion, servo-controlled abdominal venous compression with an automated inflatable binder is as effective as midodrine, the standard of care, in the management of orthostatic hypotension. Combining both therapies produces greater improvement in orthostatic tolerance. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00223691. Abstract : Supplemental Digital Content is available in the text.